Antiviral activity of four types of bioflavonoid against dengue virus type-2 - Zandi, Keivan; Teoh, Boon Teong; Sam, Sing Sin; Wong, Pooi Fong; Mustafa, Mohd Rais; AbuBakar, Sazaly (BMC, 2011)
BACKGROUND: Dengue is a major mosquito-borne disease currently with no effective antiviral or vaccine available. Effort to find antivirals for it has focused on bioflavonoids, a plant-derived polyphenolic compounds with many potential health benefits. In the present study, antiviral activity of four types of bioflavonoid against dengue virus type -2 (DENV-2) in Vero cell was evaluated. Anti-dengue activity of these compounds was determined at different stages of DENV-2 infection and replication cycle. DENV replication was measured by Foci Forming Unit Reduction Assay (FFURA) and quantitative RT-PCR. Selectivity Index value (SI) was determined as the ratio of cytotoxic concentration 50 (CC50) to inhibitory concentration 50 (IC50) for each compound. RESULTS: The half maximal inhibitory concentration (IC50) of quercetin against dengue virus was 35.7 Î¼g mL-1 when it was used after virus adsorption to the cells. The IC50 decreased to 28.9 Î¼g mL-1 when the cells were treated continuously for 5 h before virus infection and up to 4 days post-infection. The SI values for quercetin were 7.07 and 8.74 Î¼g mL-1, respectively, the highest compared to all bioflavonoids studied. Naringin only exhibited anti-adsorption effects against DENV-2 with IC50 = 168.2 Î¼g mL-1 and its related SI was 1.3. Daidzein showed a weak anti-dengue activity with IC50 = 142.6 Î¼g mL-1 when the DENV-2 infected cells were treated after virus adsorption. The SI value for this compound was 1.03. Hesperetin did not exhibit any antiviral activity against DENV-2. The findings obtained from Foci Forming Unit Reduction Assay (FFURA) were corroborated by findings of the qRT-PCR assays. Quercetin and daidzein (50 Î¼g mL-1) reduced DENV-2 RNA levels by 67 and 25, respectively. There was no significant inhibition of DENV-2 RNA levels with naringin and hesperetin. CONCLUSION: Results from the study suggest that only quercetin demonstrated significant anti-DENV-2 inhibitory activities. Other bioflavonoids, including daidzein, naringin and hesperetin showed minimal to no significant inhibition of DENV-2 virus replication. These findings, together with those previously reported suggest that select group of bioflavonoids including quercetin and fisetin, exhibited significant inhibitory activities against dengue virus. This group of flavonoids, flavonol, could be investigated further to discover the common mechanisms of inhibition of dengue virus replication.